A MANAGEMENT QUALITY SIGNAL DETECTION USING OPEN SIGNAL APPLICATION AT SEVERAL POINT LOCATIONS IN MEDAN CITY - Fitria Nova Hulu; Indra Yadi; Zumhari Zumhari; Sari Novalianda (Jurnal Ekonomi, 2022)
Technology is one thing that will continue to develop from time to time, one example of this technological development is found in telecommunications networks. Currently, we are enjoying 4G network technology. However, it turns out that the number of wireless mobile devices and services raises several challenges that cannot be solved by utilizing 4G technology, one of which is the use of spectrum. The presence of fifth-generation technology known as 5G answers challenges that cannot be solved with 4G networks. Its data capabilities are extraordinary and include all kinds of advanced features that make 5G the most powerful technology to serve large service demands.